Muddy street scene in Nome, Alaska, between 1898 and 1900 - Hester, Wilhelm, 1872-1947
Businesses identified: Discovery Saloon with Ladies entrance sign, Law offices of C. S. Johnson and Jackson & Hatch. PH Coll 318.1070 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number